Frequency and Outcomes of Hypoglycemia among Diabetic Patients Presenting to the Emergency Department - Zahid Ullah Khan, Hashmat Ullah, Shuaib Khan, Huma Rahman, Muhammed Mehran Khan, Fahad Iqbal (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Hypoglycemia is a frequent and potentially life-threatening complication of diabetes mellitus, often leading to emergency department (ED) visits and adverse clinical outcomes. Data from South Asian tertiary care settings remain limited. This study aimed to determine the frequency and short-term outcomes of hypoglycemia among diabetic patients presenting to the ED of Lady Reading Hospital, Peshawar. Objective: To determine frequency, clinical characteristics, precipitating factors, and short-term outcomes of hypoglycemia among diabetic patients presenting to emergency department. Methods: The prospective observational study was carried out between January 2022 to December 2022 and covered adult diabetic patients who reported being hypoglycemic (≤70 mg/dL). Demographic, clinical patterns, triggers, and outcomes such as hospitalization, need of ICU, relapse, hospital stay, and in-hospital fatality were documented and studied. Results: Out of 5, 842 EDs of diabetes, 412 patients experienced hypoglycemia, equating to 7.1% of the frequency. Mean age was 56.8 and 14.2 old, 54.6% were male. Diabetes type 2 was 88.3, and 62.4% were undergoing insulin-based treatment. Hypoglycemia was severe in 38.6 percent healthcare recipients. The prevalent precipitating factors were missed meals (31.3%), overdose of medicine (21.8%), kidney failure (18.0%), and infection (15.5%). All in all, 64.3 percent had to be hospitalized and 14.8 percent had to be placed in the ICU. Hypoglycemia was frequent (12.6) when hospitalized. The average days of stay was 3.9 days with a standard deviation of 2.7 days. The in-hospital mortality rate was 6.3, which was considerably high in severe hypoglycemia (12.6% vs. 2.1, p<0.001). Conclusion: Hypoglycemia represents a substantial proportion of diabetic ED visits and is strongly associated with adverse outcomes, particularly in severe cases. Keywords: Hypoglycemia, Diabetes mellitus, Emergency department, Insulin therapy, Intensive care unit, Mortality.